Assignment 3

course Mth 174

b}¸ý̿؉¿¾ƒ®¾À‘ûŠÀÓÕassignment #003

¹šØ¯ÿ”`˜âSû‡«¬B©ÀÂàÄÚø

Physics II

06-05-2009

......!!!!!!!!...................................

11:15:52

query 6.5 #8 Galileo: time for unif accel object to traverse dist is same as if vel was ave of init and final; put into symbols and show why true

......!!!!!!!!...................................

RESPONSE -->

I understood what the statement was saying but it was difficult for me to be able to put it into symbols but this is what I came up with:

-gt + v0t + s0 = (-gt^2)/2 + v0t + s0

** Using s for the distance

fallen we can translate Galileo's statement as follows:

 

 

An object accelerating for

time t, starting with initial velocity v0 at t = 0, has velocity function

 

 

and position function

 

 

assuming that s = 0 at t =

0.

 

Both of these results are

easily obtained, for the given initial condition that initial velocity is zero,

by a straightforward integration of the acceleration function (to get the

velocity function) then the velocity function (to get the position function).

 

 

For given displacement s we

can solve the position equation for t.  The equation is rearranged to the form

of a standard quadratic:

 

.5 a t^2 + v0 t – s = 0,

with solutions

 

 

Substituting this into the

velocity function we obtain the final velocity:

 

Final velocity

= v0 + a t = v0 + a *

(-v0 +- sqrt(v0^2 + 2 a s) / a)

= +- sqrt(v0^2 + 2 a s)

.

 

The average of the initial

and final velocities is therefore

 

 

Traveling at this velocity

for time t = (-v0 +- sqrt(v0^2 + 2 a s) ) / a ) the displacement will be

 

= ( v0 +- sqrt(v0^2 + 2

a s)) (-v0 +- sqrt(v0^2 + 2 a s) ) / a ) / 2

 

The numerator is the product

of the sum and the difference of two quantities and simplifies to 2 a s.  The

denominator is 2 a so the expression simplifies to just s.

 

This confirms that the

distance traveled is the same as the distance that would be traveled at the

average of the initial and final velocities.

 

 

 

Alternative solution:

 

For uniform acceleration the

velocity function can be expressed as

 

 

Integrating this function

between clock times t1 and t2 we obtain the displacement s:

 

 

Dividing the integral

(i.e., the displacement) by the length of the interval

we get the average value of the function—i.e., the average velocity.  The length

of the interval is t2 – t1 so

 

Integral / interval =

 

(1/2 a (t2^2 – t1^2) +

v0 ( t2 – t1)) / (t2 – t1) =

 

1/2 a ( t2 + t1) + v0. 

 

The initial value of the

velocity on the interval is v0 + a t1, the final velocity v0 + a t2, so the

average of initial and final velocities is

 

(v0 + a t1 + v0 + a t2)

/ 2 =

 

v0 + 1/2 a ( t1 + t2).

This is

identical to the expression obtained previously.

 

Thus the average of the

initial and final velocities is equal to the average velocity on the interval,

and the result is proven.</h3>

 

 

 

Still another

solution:

 

If an object is dropped from

rest and falls for time t it will reach velocity vf = a t.  So the average of

its initial and final velocities will be

 

The distance fallen is

known to be

 

 

But this is exactly the distance

the object would travel in time t if its average velocity was 16 t.  Thus

the two quantities are identical.

 

 

A

numerical example for a given s:

 

When s = 100, then, t is the

positive solution to 100 = 16 t^2.  This solution is t = 2.5.

 

The velocity function is v =

a t.  We have to find v when s = 100.  When s = 100, we have t = 2.5, as just

seen.  So v = a t = 32 * 2.5 = 80, representing 80 ft/sec.

 

Now we know that s = 100, vf

= 80 and v0=0.  Substituting into t = s / [ (vf + v0)/2 ] we get t = 100 / [ (80

+ 0) / 2 ] = 100 / 40 = 2.5.

 

This agrees with the t we

got using s = .5 a t^2.  **

 

 

 

Another

argument:

 

The average value of any

linear function over an interval is equal to the average of its initial and

final values over the interval. 

 

In a nutshell, because the v

vs. t graph is linear, the average velocity is equal to the average of the

initial and final velocities. 

 

Since

 

  time of fall =

displacement / average velocity,

 

it follows that

 

  time of fall =

displacement / (ave of initial and final vel).

 

This latter expression is

just the time that would be required to fall at a constant velocity which is

equal to the average of initial and final velocities.

 

More rigorously:

 

The graph is linear, so the

area beneath the graph is the area of a triangle. 

 

The base of the triangle is

the time of fall, and its altitude is the final velocity.

 

By a simple construction we

know that the area of the triangle is equal to the area of a rectangle whose

length is equal to the base of the triangle, and whose width is equal to half

the altitude of the triangle.

 

It follows that the area of

the triangle is equal to half the final velocity multiplied by the time

interval.

 

Since the initial velocity

is 0, the average of initial and final velocities is half the final velocity.

 

So the area of the triangle

is the product of the time of fall and the average of initial and final

velocities

 

  area beneath graph = time

of fall * ave of init and final vel

 

The area beneath the graph

is equal to the integral of the velocity function over the time interval, which

we know is equal to the displacement.  So we have

 

  displacement = time of

fall * ave of init and final vel, so that

  time of fall =

displacement / ave of init and final vel.

 

This leads to the same

conclusion as above.

 

 

 

The same argument, expressed

more

symbolically:

 

A graph of v vs. t graph is

linear.  Over any time interval t = t1 to t = t1 + `dt, displacement is

represented by the area of the corresponding trapezoid, which is d = (v1 + v2) /

2 * `dt. 

 

Solving for `dt we again

obtain `dt = d / [ (v1+v2)/2 ].

 

.................................................

......!!!!!!!!...................................

11:17:53

how can you symbolically represent the give statement?

......!!!!!!!!...................................

RESPONSE -->

-gt + v0t + s0 = (-gt^2)/2 + v0t + s0

I used part b of the problem to show why this is true. Since the object dropped from a 100ft building accelerating from rest:

-32(0) + (0) + 100 = (-32(0))/2 + (0) + 100

100 = 100

.................................................

......!!!!!!!!...................................

11:17:58

How can we show that the statement is true?

......!!!!!!!!...................................

RESPONSE -->

-gt + v0t + s0 = (-gt^2)/2 + v0t + s0

I used part b of the problem to show why this is true. Since the object dropped from a 100ft building accelerating from rest:

-32(0) + (0) + 100 = (-32(0))/2 + (0) + 100

100 = 100

.................................................

......!!!!!!!!...................................

11:19:05

How can we use a graph to show that the statement is true?

......!!!!!!!!...................................

RESPONSE -->

You can make a graph with the x-axis being position and the y-axis being time.

.................................................

......!!!!!!!!...................................

11:30:43

query problem 7.1.22 (3d edition #18) integral of `sqrt(cos(3t) ) * sin(3t)

......!!!!!!!!...................................

RESPONSE -->

integral of `sqrt(cos(3t) ) * sin(3t)

u= cos3t, du= -sin3t dx

the derivative of cos(3t) is -3 sin(3t)

- integral of (u)^1/2 du =

- 2/3 (u) ^3/2 du=

-2/3 (cos3t)^3/2 + C

To perform the integral use

substitution.  Very often the first substitution you want to try involves the

inner function of a composite, and that is the case here.  Cos(3t) is the inner

function of the composite sqrt(cos(3t)), so we try using this as our

substitution:

 

w = cos (3t)    dw = -3 sin

(3t)

 

so that sin(3t) = -dw / 3.

 

Thus our expression becomes

 

w^(1/2) * (-dw / 3).

 

The integral of -1/3 w^(3/2)

with respect to w is -1/3 * (2/3) w^(3/2), treating w^(1/2) as a power function.

 

This simplifies to

 

-2/9  w^(3/2) or

-2/9 * (cos(3t))^(3/2).

 

The general antiderivative

is

 

-2/9 * (cos(3t))^(3/2) + c,

 

where c is an arbitrary

constant.**

.................................................

......!!!!!!!!...................................

11:31:56

what did you get for the integral and how did you reason out your result?

......!!!!!!!!...................................

RESPONSE -->

integral of `sqrt(cos(3t) ) * sin(3t)

u= cos3t, du= -sin3t dx

- integral of (u)^1/2 du =

- 2/3 (u) ^3/2 du=

-2/3 (cos3t)^3/2 + C

I used u=cos3t because 3t is not a seperate function and the derivative is part of the original problem (sin3t).

Note that the derivative of -2/3 (cos3t)^3/2 + C is 3 cos(3t), not cos(3t).

cos(3t) is a composite function and it's necessary to use the chain rule.

.................................................

......!!!!!!!!...................................

11:35:10

query problem 7.1.20 (3d edition #21) antiderivative of x^2 e^(x^3+1)

......!!!!!!!!...................................

RESPONSE -->

antiderivative of x^2 e^(x^3+1)

u=x^3 + 1, du= 3x^2dx so du/3 = 1/3

1/3 integral of e^u du =

1/3 e^ (x^3 1) + C

.................................................

......!!!!!!!!...................................

11:35:15

what is the antiderivative?

......!!!!!!!!...................................

RESPONSE -->

antiderivative of x^2 e^(x^3+1)

u=x^3 + 1, du= 3x^2dx so du/3 = 1/3

1/3 integral of e^u du =

1/3 e^ (x^3 1) + C

.................................................

......!!!!!!!!...................................

11:35:27

What substitution would you use to find this antiderivative?

......!!!!!!!!...................................

RESPONSE -->

u=x^3 + 1, du= 3x^2dx so du/3 = 1/3

.................................................

......!!!!!!!!...................................

12:06:43

query problem 7.1.37 (3d edition #35) antiderivative of (t+1)^2 / t^2

......!!!!!!!!...................................

RESPONSE -->

I tired different ways to get the answer that was in the back of the book, t + 2lnt - 1/t + C, and could never reach it. I tried u= t+1 du = 1dx and t = u - 1but ended up with

integral of (u)^2 / (u - 1) ^2 =

u^2 (u - 1)^2du=

-1/3 (t + 1)^3 (t + 1)^-1 + C

I also tried u=t^2, du = 2tdx and ended up with:

1/2 integral of (t + 1) ^2 / u =

1/2 lnu (t + 1)^2 =

1/2 lnt^2 1/3(t + 1) ^3=

1/5 ln t^2 ( t + 1) ^3 + C

I think whatever I am doing wrong here is the same problem I had with other problems in the book. When do you solve for the variable with u?

expand (t+1)^2 to get t^2+2t+1.

 

divide by t^2 to get 1 + 2t^-1 + t^-2.

 

Each term of this function is a power function. Integrate term-by-term and add the integration constant to get the general antiderivative

 

general antiderivative = t + 2ln(t) - t^-1 +C

.................................................

......!!!!!!!!...................................

12:06:47

what is the antiderivative?

......!!!!!!!!...................................

RESPONSE -->

.................................................

......!!!!!!!!...................................

12:06:51

What substitution would you use to find this antiderivative?

......!!!!!!!!...................................

RESPONSE -->

.................................................

......!!!!!!!!...................................

12:15:24

query 7.1.64 (3d edition #60). int(1/(t+7)^2, t, 1, 3)

......!!!!!!!!...................................

RESPONSE -->

int(1/(t+7)^2=

u= t + 7

du = 1dx

when t = 1, u = 8

when t = 3, u =10

= du / (u^2) dx = lnIu^2I = ln I10^2I - ln I8^2I = .4462

This situation involves a composite of the power function 1 / z^2 and the linear function t + 7. The latter is the ‘inner’ function of the composite.

 

We therefore substitute u = t+7 to get du = dt; limits t = 1 and t = 3 become u = 8 and u = 10. So the integral becomes

 

integral( u^-2, u from 8 to 10).

 

The integrand is the power function u^-2, or 1 / u^2. Its simplest antiderivative can be expressed as -u^-1 or -1/u.

 

So the definite integral is

change in antiderivative =

-1/10 - (-1/8) =

1/8 - 1/10 =

1/40.

.................................................

......!!!!!!!!...................................

12:15:29

What did you get for the definite integral?

......!!!!!!!!...................................

RESPONSE -->

int(1/(t+7)^2=

u= t + 7

du = 1dx

when t = 1, u = 8

when t = 3, u =10

= du / (u^2) dx = lnIu^2I = ln I10^2I - ln I8^2I = .4462

.................................................

......!!!!!!!!...................................

12:15:42

What antiderivative did you use?

......!!!!!!!!...................................

RESPONSE -->

when t = 1, u = 8

when t = 3, u =10

.................................................

......!!!!!!!!...................................

12:15:58

What is the value of your antiderivative at t = 1 and at t = 3?

......!!!!!!!!...................................

RESPONSE -->

int(1/(t+7)^2=

u= t + 7

du = 1dx

when t = 1, u = 8

when t = 3, u =10

= du / (u^2) dx = lnIu^2I = ln I10^2I - ln I8^2I = .4462

.................................................

......!!!!!!!!...................................

12:18:16

query 7.1.86. World population P(t) = 5.3 e^(0.014 t).

......!!!!!!!!...................................

RESPONSE -->

.................................................

......!!!!!!!!...................................

12:21:54

What were the populations in 1990 and 2000?

......!!!!!!!!...................................

RESPONSE -->

P = 5.3e^.014t

P= 5.3 e^.014t

It would stay the same for 1990 because t already = time since 1990. t= 10 for 200 because it is 10 years after 1990 so:

P = 5.3e^.014(10)

P= 5.3e^ .14

.................................................

......!!!!!!!!...................................

12:34:04

What is the average population between during the 1990's and how did you find it?

......!!!!!!!!...................................

RESPONSE -->

Integral from 10 to 1 of 5.3 e^.014t

u= .014t

du = .014 dx = du/.014 = 1/.014

when t = 10, u = .14

when t = 1, u = .014 so

1/.014 integral from .14 to .014 of 5.3e^ u du =

1/.014 * 5.3^u du =

2650 / 7 e^u =

2650 / 7 e ^ .014t =

(2650 / 7 e^ .014 * .14) - (2650 / 7 e^ .014 * .014) =

379.314 - 378.645 = .669 billion

In

1990, t = 0 so the population is

P(0) =
5.3 billion

In 2000,

t = 10 so the population is

P(10) =
 6.1 billion

 

To find

the average population we integrate the population function over the 10-year

interval, then divide by the 10 years:

 

An antiderivative of 5.3

e^(0.014 t) is found by letting u equal the ‘inner function’ of the composite:

 

u = .014 t so

du = .014 dt and

dt = du / .014.

 

Thus the expression 5.3

e^(0.014 t) dt becomes 5.3 e^u * du / .014.

 

An antiderivative of e^u

with respect to u is just e^u, so the antiderivative of the function is

 

 

At t = 0 this antiderivative

would have value about 380.

 

At t = 0 your antiderivative

would have value about 435.

 

 

The average value of

the function is equal to its definite integral divided by the time interval:

 

This is quite close to,

but a little less than the average of the initial and final

populations.

 

It is less because

the exponential function is concave upward, and the population

curve
therefore 'dips' below the straight line connecting the

initial and final points
.

 

However the curvature

on this interval is not pronounced, and the function never

'dips' far below the straight line, so the average is

close

to
the straight-line average you gave in your

initial solution
.</h3>

 

 

INCORRECT

IF NOT UNREASONABLE ANSWER: 

 

The

average population seems as if it would be the average of the two, therefore

 

6.1 + 5.3/ 2 = 5.7

billion

 

INSTRUCTOR RESPONSE:

 

Review the definition of the

average value of a function:

 

Now if

the function is linear, then the average of its initial

and final values
is equal to its average value (see the above

given solution to the Galileo problem).  However:

 

The exponential function

is not linear, and is in fact concave upward

on this interval,
so averaging initial and

final values on the interval
won't work here.

 

You have to integrate

the function and divide by the 10-year interval of integration

.................................................

......!!!!!!!!...................................

12:35:00

What is the value of your antiderivative at t = 1 and at t = 3?

......!!!!!!!!...................................

RESPONSE -->

I used t = 1 and t = 10 since there are 10 years difference in 1990 and 2000.

.................................................

......!!!!!!!!...................................

12:36:05

Query Add comments on any surprises or insights you experienced as a result of this assignment.

......!!!!!!!!...................................

RESPONSE -->

.................................................

&#Your work looks good. See my notes. Let me know if you have any questions. &#

Self-critique Rating:

2

"